Political coup from Pakatan Harapan to Perikatan Nasional: a nightmare tragedy during pandemic Covid-19 - Syed Sopi, Saiyid Radzuwan (Advances in Humanities and Contemporary Studies, 2022)
The power transition from Alliance of Hope (Pakatan Harapan - PH) to National Alliance (Perikatan Nasional - PN) is a nightmare and the defections of several MPs from PH to PN are worsening the Malaysian political scenario. The downfall of PH could be explained how Mahathir had manipulated the PH loyalty in making a decision without consulting its coalition members. The fall of PH is not a strange scenario, but Mahathir’s role itself had played as a kingmaker in the collapse of his own administration. Besides that, PN has been portrayed by opponents as a ‘backdoor power grab’ and PN led by Muhyiddin has created simple narrative due to stay in power: political corruption is used as a bribe to silence coalition members from revolting and the Movement Control Orders (MCOs) due to Covid-19 pandemic and the announcement of emergency ordinance 2021 throughout Malaysia from 11 Jan 2021 to 1 August 2021 imposed by Muhyiddin has strengthened his position. Therefore, this research found that Muhyiddin could give thousands of reasons why he needs to implement an emergency order and many opposition MPs asserted that Muhyiddin’s reasoning is just a political rhetoric to allow him to stay in power.